Demographics, management, and welfare of nonracing horses in Prince Edward Island - Christie, Julie L. (Canadian Veterinary Medical Association, 2004)
There are no detailed, representative, horse-level data about equine management practices in different parts of Canada. To help address this, the demographics, management, and welfare of 312 nonracing horses in Prince Edward Island were examined in a randomized, horse-level survey during summer 2002. Owners completed a pretested questionnaire, and a veterinarian examined each horse. Owners were experienced caregivers and the horses were generally in good condition. Areas for improvement included parasite control, dental and hoof care, and tail docking. The mean fecal egg count was 428 eggs per gram; 76% of owners never removed manure from the pasture. Sixty-two percent of horses had never had a veterinary dental examination. Many horses had hoof defects (excessively long hooves, 26.8%; hoof wall breaks, 32.0%; and white line disease, 8.5%). Many (54.9%) draft horses had docked tails. These results suggest owners might benefit their horses by receiving education in aspects of equine care.